Srikandi Application: Digital Innovation for Dynamic Archive Management - Putri, Dwi Rahma; Subagja, Resa; Wulandari, Sri; Nurfalah, Farida (ann4publisher@gmail.com, 2025)
Background. The Indonesian government developed the Srikandi application to manage dynamic archives on a national scale. The management of the Srikandi application has been regulated in the National Archives Regulation of the Republic of Indonesia Number 4 of 2021 concerning Guidelines for the Implementation of an Integrated Dynamic Archive Information System. Aims. The purpose of this study is to investigate the application of Srikandi in Disarspus Kuningan Regency, the obstacles encountered, and the efforts made, utilizing the Dynamic Archive Theory, as proposed by Basuki, which encompasses 7 dimensions. The creation and implementation of the filing system, along with the utilization of digital imaging technology, are two key dimensions that have been applied to the Srikandi application. Dynamic archive retention, inactive dynamic archive storage, vital dynamic archive protection, form management, and report management are dimensions that have not been implemented in the Srikandi application for the Kuningan Regency Archives. Method. This study uses a descriptive-qualitative method. Data was collected through interviews, observations, and documentation. Result. Archived by Kuningan Regency, the Srikandi application has only been implemented since 2024, but its implementation is still not optimal. Conclusion. The obstacles experienced by the Kuningan Regency Archives are disruptions to the central server, a lack of notification features, old employee factors, and miscommunication between employees and agency heads. Implementation. Efforts have been made by the Kuningan Regency Archives, namely by conducting manual correspondence, checking the Srikandi application periodically, sending young employees in Srikandi application training, and providing briefings to employees and agency heads.